THE ANALYSIS OF THE EFFECTIVENESS OF TAX COLLECTION OF NON METALLIC MINERALS AND ROCKS BASED ON TAX ASSESSMENT SYSTEM AND ITS CONTRIBUTION TO OWN-SOURCE REVENUE IN BITUNG CITY - Wangka, Melisa Fransisca; Mawikere, Lidia (Universitas Sam Ratulangi, 2015)
Regional Income is a source regional finance and government funding. One way to meet admission finance government spending is to optimize revenues from the sector of local taxes. From several types of local taxes one to be concerned of the government of Bitung is the Non Metallic Minerals and Rocks Taxes. This study was conducted to determine the level of effectiveness and contribution of Non Metallic Minerals and rocks tax is a source of revenue in Bitung. The study was conducted in Bitung City Regional Revenue Office. The analytical method used is descriptive quantitative method, which analyzes the target data and the realization of tax revenues Non Metallic Minerals and Rocks in 2011-2014 by using the ratio of the effectiveness and contribution. The results shows that the level of effectiveness of Non Metallic Minerals and rocks tax in 2011, 2012, 2013, and 2014 meet the criteria of Highly Effective. Contributions of Non Metallic Minerals and rocks tax as a source of revenue for the past four years and a maximum rated is not included in the criteria for contributions Very poorly. The percentage does not reach 5%. System voting should be considered and rectified by Bitung City Government , so that tax revenue of Non Metallic Minerals and rocks will be more effective and able to contribute even more. Keywords: minerals tax, regional income, effectiveness